ANALISIS RASIO LIKUIDITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT ADHI KARYA (PERSERO) TBK JAKARTA - Pri Pantjaningsih (POLITEKNIK LP3I JAKARTA, 2019)
This thesis was written by Amelia Priscila, in August 2018 until October 2018, with the title: Analysis Of Liquidity And Profitability Ratio To Assess Financial Performance At PT Adhi Karya (Persero) Tbk Jakarta.This study aims to obtain information on liquidity ratios and profitability to assess financial performance. And obtaining information on how much liquidity and profitability ratios are used to assess financial performance.The research method used in this study is quantitative descriptive with secondary data sources in the form of balance sheet and income statement of PT Adhi Karya (Persero) Tbk for the 2013-2017 period. Data collection techniques by means of library research and documentation studies.Based on the results of financial performance analysis with a measure of liquidity ratios and profitability ratios, it is known that the valuation of the company still does not meet the industry ratio standards. For the liquidity ratio, the average current ratio is 1.4 times, the average quick ratio is 1.2 times, the average cash ratio is 27%, the average cash turn over is 33%, and the average inventory to net working capital is 47% classified as good. For the profitability ratio, the average net profit margin is 4%, the average return on investment is 3%, and the average return on equity is 14%. Keywords: liquidity ratio, profitability ratio